The bioproductive behavior of breeding sows and their offspring fed with probiotic additive - Miranda-Yuquilema, José Efraín; Marin-Cárdenas, Alfredo; González-Pérez, Mabel (Revista de Ciencias Agrícolas, 2018)
Probiotic additives contain beneficial microorganisms that included in the diet, in sufficient quantities, have a positive effect on the health of the host. However, high costs have limited its use in pork producers in developing countries. With the objective of evaluating the bioproductive behavior in breeding sows and their offspring when bioprepared in the diet is complemented. We used 12 hybrid breeding sows CC21 (Yorkshire-Landrace/L35 Duroc) and their descendants, divided into two groups of six animals each. T1, control and T2, treatment. T2, contained Lactobacillus acidophilus, Streptococcus thermophilus and Kluyveromyces fragilis (L-4 UCLV). A completely randomized design was used, the weight gained and the reproductive behavior in the offspring were evaluated; Weight gain in piglets from birth to pre-fattening, diarrheal cases and mortality, and the morpho-teintorial characterization of the microorganisms from the rectal swab. The weight gain in mother sows and piglets was higher (P>0.05) in T2. The diarrheic cases and mortality were lower (P<0.05) in T2; with the morpho-teintorial characterization, higher microbial load (P<0.05) was observed mainly coconuts in chain and isolated, short and chain bacilli positive gram and yeasts. It is concluded that the inclusion of bioprepared in the diet of the breeding sows and their offspring improves the bioproductive behavior, reduces diarrhea and deaths and increases the microbial load with corresponding morpho-teintorial characteristic to Bacilli, gram-positive cocci and yeasts.